2016
DOI: 10.1016/j.physbeh.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute alcohol withdrawal on nest building in mice selectively bred for alcohol withdrawal severity

Abstract: Nest building has been used to assess thermoregulatory behavior and positive motivational states in mice. There are known genetic influences on ethanol withdrawal severity as well as individual/thermoregulatory nest building. Withdrawal Seizure-Prone (WSP-1, WSP-2) and Withdrawal Seizure-Resistant (WSR-1, WSR-2) mice were selectively bred for high vs low handling-induced convulsion (HIC) severity, respectively, during withdrawal from chronic ethanol vapor inhalation. They also differ in HIC severity during wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Mice selectively bred for severe chronic EtOH withdrawal HICs had reduced home cage activity lasting up to 24 h after withdrawal in a study using chronic EtOH vapor methods similar to those used here [29]. However, these mice showed nest-building deficits lasting up to 32 h after acute EtOH withdrawal, a time when we did not observe decreased locomotor activity [30]. In this manuscript, we discuss several other studies that dissociate nest-building deficits from changes in locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mice selectively bred for severe chronic EtOH withdrawal HICs had reduced home cage activity lasting up to 24 h after withdrawal in a study using chronic EtOH vapor methods similar to those used here [29]. However, these mice showed nest-building deficits lasting up to 32 h after acute EtOH withdrawal, a time when we did not observe decreased locomotor activity [30]. In this manuscript, we discuss several other studies that dissociate nest-building deficits from changes in locomotor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we also observed that animals from ethanol condition built nests with poorer quality. Several studies have suggested that decreased nest building in small mammals reflects an anhedonic state [ 41 ], and this score has also been shown to be sensitive to EtOH withdrawal severity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nest building behavior in mice has been utilized as an assay for affective states as well as sensorimotor function and these entities are modified even during acute ethanol withdrawal. 89 The hippocampus plays an important role in nest building and hippocampal lesions lead to impairment of this behavior. 90–92 In addition, to acute ethanol withdrawal, abstinence from chronic ethanol predictably modulates nest-building behavior 93 and this is substantiated by our results.…”
Section: Discussionmentioning
confidence: 99%